Analogies between reading of medical and religious texts. Issue 7577 (16th November 2006) - Links, Matthew
Abstract : Whether you take a fundamental or liberal view of scientific evidence will affect how you interpret it. But just as with religion, we need to admit there will be legitimate differences in our views